Moral Development and Moral Reasoning Research in Children and Adolescents With Intellectual Disability – Historical Overview - Milićević, Milena; Potić, Srećko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
The aim of this paper was to make an overview of studies focused on the determination and identification of factors and determinants of moral reasoning of children and adolescents with intellectual disability. The available literature review was conducted from a historical point of view. Descriptions of identified characteristics and factors of importance were provided in order to understand the nature and extent of their impact on moral development. The knowledge in this field was systematized by the analysis of selected studies. Results of 15 research studies presented here suggest that children and adolescents with intellectual disability do not progress through developmental stages at the same speed and tempo as their peers without intellectual disability, nor do they reach higher stages of moral development. Understanding the complexity and diversity of the impact of allocated factors on moral development requires a broader focus than just their determination.